2021
DOI: 10.1177/08850666211018982
|View full text |Cite
|
Sign up to set email alerts
|

Does Targeted Temperature Management Improve Neurological Outcome in Extracorporeal Cardiopulmonary Resuscitation (ECPR)?

Abstract: Purpose: Targeted temperature management (TTM) is a standard of care in patients after cardiac arrest for neuroprotection. Currently, the effectiveness and efficacy of TTM after extracorporeal cardiopulmonary resuscitation (ECPR) is unknown. We aimed to compare neurological and survival outcomes between TTM vs non-TTM in patients undergoing ECPR for refractory cardiac arrest. Methods: We searched PubMed and 5 other databases for randomized controlled trials and observational studies reporting neurological outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 38 publications
1
18
0
Order By: Relevance
“…There has been continued interest in targeted temperature management (TTM) and hypothermia for ECPR patients, with evidence both for and against targeted normothermia and hypothermia. 23–26 A meta-analysis of ECPR studies has suggested that there is no difference in neurologic outcome between patients subjected to TTM versus non-TTM practices, 27 and we echo this finding for our cohort’s neurologic outcome, ABI, and mortality. There is a paucity of multicenter studies examining PaCO 2 and ABI specifically in ECPR patients, and a larger sample would permit multivariable analysis using temperature, PaCO 2 , and CPR practices.…”
Section: Discussionsupporting
confidence: 72%
“…There has been continued interest in targeted temperature management (TTM) and hypothermia for ECPR patients, with evidence both for and against targeted normothermia and hypothermia. 23–26 A meta-analysis of ECPR studies has suggested that there is no difference in neurologic outcome between patients subjected to TTM versus non-TTM practices, 27 and we echo this finding for our cohort’s neurologic outcome, ABI, and mortality. There is a paucity of multicenter studies examining PaCO 2 and ABI specifically in ECPR patients, and a larger sample would permit multivariable analysis using temperature, PaCO 2 , and CPR practices.…”
Section: Discussionsupporting
confidence: 72%
“…Post-resuscitation hyperthermia should be avoided [ 145 ]. The timing of ECPR and the optimum target temperature following ECPR, are unknown [ 152 , 153 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Targeted temperature management (TTM) is recommended for patients with out-of-hospital cardiac arrest (OHCA) who remain comatose after the return of spontaneous circulation (ROSC) [1,2]. In the setting of extracorporeal membrane oxygenation (ECMO) for OHCA, TTM was also associated with good neurological outcomes and is recommended in the Extracorporeal Life Support Organization guidelines [3][4][5][6][7]. Attempts at improving cardiac arrest care have seen an increase in the use of ECMO, which, when combined with TTM, is an intensive care strategy requiring a large investment in logistics [8].…”
Section: Introductionmentioning
confidence: 99%